2021
DOI: 10.3390/ijerph18031220
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption during a Pandemic Lockdown Period and Change in Alcohol Consumption Related to Worries and Pandemic Measures

Abstract: Whether lockdown related to the COVID-19 pandemic influences alcohol consumption is not well known. This study assesses alcohol consumption and hazardous drinking behavior during the initial phase of pandemic measures in Norway and identifies potential risk factors. A cross-sectional study (N = 25,708) was conducted in Bergen, Norway, following the first six weeks of strict infection control measures. In a model of self-assessed increased alcohol consumption, logistic regression analysis was conducted with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
89
4
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 41 publications
16
89
4
11
Order By: Relevance
“…The findings also revealed frequent sedentary behaviors, unhealthy food intake, alcohol consumption, and reduction of physical activity during the COVID-19. All these unhealthy habits showed negative associations with worsening of emotional status, corroborating results of other publications [26][27][28]50]. On the other hand, the regular intake of fruits and vegetables as well as the practice of physical activity during the pandemic showed a positive influence on emotional well-being in line with previous evidence [51].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings also revealed frequent sedentary behaviors, unhealthy food intake, alcohol consumption, and reduction of physical activity during the COVID-19. All these unhealthy habits showed negative associations with worsening of emotional status, corroborating results of other publications [26][27][28]50]. On the other hand, the regular intake of fruits and vegetables as well as the practice of physical activity during the pandemic showed a positive influence on emotional well-being in line with previous evidence [51].…”
Section: Discussionsupporting
confidence: 89%
“…Anxiety, depression, loneliness, and poor sleep quality are the most common psychological problems [22][23][24][25]. Several modifiable risk and protective factors have been identified in adolescents, with better nutritional status and regular practice of physical activity associated with lower levels of depressive and anxiety symptoms, as well as better sleep quality [26,27], whereas alcohol consumption was associated with higher levels of mental health problems [28]. Moreover, evidence of socioeconomic inequalities has been found for both mental health and healthy lifestyles, and it invariably shows unfavorable data regarding adolescents of disadvantaged families [19,29].…”
Section: Introductionmentioning
confidence: 99%
“…During the first months of the COVID-19 pandemic, many survey studies found that a large proportion of current drinkers reported they had changed their consumption, either by drinking less or by drinking more [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In most of these studies, the proportion having decreased their consumption was larger than that reporting increased consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Garnett et al (2021) found about the same proportion of UK adults (25%) reporting drinking more and less alcohol than usual during the COVID-19 related lockdown with those younger, female, of high socioeconomic position, suffering from an anxiety disorder, and stressed about finances or COVID-19 to be at greater risk. Others studies in the UK and Norway indicate that increased alcohol use and misuse were associated with psychological, social and economic stress and vulnerability (Alpers et al, 2021;Naughton et al, 2021).…”
Section: Changes In Alcohol Use During the Covid-19 Health Emergencymentioning
confidence: 97%